The ethics and law of safeguarding. (2nd January 2023) - Ellis, Hannah; Ellis, Emily; Ellis, Peter
Abstract : Hannah Ellis, Emily Ellis and Peter Ellis discuss the ethics of safeguarding arising from the principles of healthcare ethics and consequentialism.